An exploration of the semantic network in Alzheimer's disease: Influence of emotion and concreteness of concepts. (August 2015) - Giffard, Bénédicte; Laisney, Mickaël; Desgranges, Béatrice; Eustache, Francis
Abstract: Semantic deficits are often reported in even the very early stages of Alzheimer's disease (AD), but investigations usually focus on concrete and non-emotional entities, ignoring the broad range of concepts that feature in everyday conversations. Emotional concepts (e.g., snake ) have been found to be processed more accurately than neutral ones (e.g., chair ) in AD. Our aim here was therefore to explore the dimensions of both concreteness and emotion within the semantic framework, and in particular to determine whether abstract emotional words (e.g., grief ) are processed as accurately as concrete emotional ones (e.g., snake ) in AD. We administered a semantic priming (SP) task (lexical decision), yielding an implicit measurement of semantic memory, to 15 patients with AD and 31 normal controls. Concrete and abstract word pairs either shared a semantic relationship (e.g., table-chair, motive-reason ), a semantic and emotional relationship (e.g., snake-viper ; grief-sadness ), or no relationship at all (e.g., pencil-horse ). On the basis of response time differences between these conditions, we obtained four SP scores: concrete neutral SP, abstract neutral SP, concrete emotional SP, and abstract emotional SP. In the AD group, the SP score for abstract neutral concepts was not significant, and significantly below the other three SP scores, that seems to reflect a major deterioration in these concepts. An abnormal hyperpriming effect was observed in the concrete neutral SP condition (SP score significantly higher than that of controls), reflecting a partial deterioration in these concepts. These results suggest that, without an emotional relationship, abstract words deteriorate more quickly than concrete words. No such dissociation linked to the concreteness effect was observed with emotional words. Therefore, in AD, emotional concepts would be affected later, be they concrete or abstract.